2002
DOI: 10.1103/physrevlett.88.195701
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Time-Temperature Transformation and the Liquid-Liquid Phase Transition in Water

Abstract: We study the TIP5P water model proposed by Mahoney and Jorgensen, which is closer to real water than previously-proposed classical pairwise additive potentials. We simulate the model in a wide range of deeply supercooled states and find (i) the existence of a non-monotonic "noseshaped" temperature of maximum density line and a non-reentrant spinodal, (ii) the presence of a low temperature phase transition, (iii) the free evolution of bulk water to ice, and (iv) the timetemperature-transformation curves at diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
205
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(237 citation statements)
references
References 25 publications
30
205
1
1
Order By: Relevance
“…What has been proved is that computer simulations using tried and tested models of liquid water confirm the broad features of this phase diagram (see Ref. [12] and references therein). But computer models of water (like computer models of anything) are Current experiments on this problem are of two sorts.…”
Section: Article In Pressmentioning
confidence: 96%
See 1 more Smart Citation
“…What has been proved is that computer simulations using tried and tested models of liquid water confirm the broad features of this phase diagram (see Ref. [12] and references therein). But computer models of water (like computer models of anything) are Current experiments on this problem are of two sorts.…”
Section: Article In Pressmentioning
confidence: 96%
“…Next we explore the hypothesis [50] that the observed glass transition in biomolecules [12,[51][52][53][54][55][56][57][58][59][60][61][62][63]71] is related to the liquid-liquid phase transition using MD simulations. Specifically, Kumar et al [50] studied the dynamic and thermodynamic behavior of lysozyme and DNA in hydration TIP5P water, by means of the software package GROMACS [64] for: (i) an orthorhombic form of hen egg-white lysozyme [65] and (ii) a Dickerson dodecamer DNA [66] at constant pressure P ¼ 1 atm, several constant temperatures T, and constant number of water molecules N (NPT ensemble).…”
Section: Glass Transition In Biomoleculesmentioning
confidence: 99%
“…It was found that ice nucleation occurs when a sufficient number of relatively long-lived hydrogen bonds develop spontaneously at the same location to form a fairly compact initial nucleus. At a high density, crystallization takes place more easily [223]. Ice nucleation was also reported by metadynamics simulations [224] and replica-exchange umbrella sampling [225] in the isothermal-isobaric ensemble; however, the results may depend on the choice of order parameters.…”
Section: Local Structural Ordering and Homogeneous Crystal Nucleationmentioning
confidence: 98%
“…Refs. [12,13,14,15,16]). Current conventional MD simulations typically are able to study systems of a few thousand molecules over a time scale of tens of nanoseconds.…”
Section: Introductionmentioning
confidence: 99%